1989
DOI: 10.1007/bf01092066
|View full text |Cite
|
Sign up to set email alerts
|

Dry heat popping of amaranth seed might damage some of its essential amino acids

Abstract: Amaranth was a major crop among the Aztecs. In Mexico the seed is popped and eaten with brown sugar. The crude protein content of the seed is 14 +/- 2% but its contents of lysine and tryptophan are 6.2 and 1.6 g/16 g N respectively. We developed a popping method based on a fluid bed system (FBS) whereas the traditional method (TM) is just to pop the seeds manually in a hot plate. Assays carried out were evaluation of racemization of the amaranth protein due to heat treatment, amino acid composition of the raw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 18 publications
3
21
0
1
Order By: Relevance
“…Pant (1985) stated the decrease of lysine level by 36% (from 4.83 to 3.08 g/16 g N) in traditionally popped grain while in commercially popped grain the lysine level decreased by 25%. Tovar et al (1989) found the decrease of lysine, arginine and cystine levels while using both the methods of popping.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pant (1985) stated the decrease of lysine level by 36% (from 4.83 to 3.08 g/16 g N) in traditionally popped grain while in commercially popped grain the lysine level decreased by 25%. Tovar et al (1989) found the decrease of lysine, arginine and cystine levels while using both the methods of popping.…”
Section: Resultsmentioning
confidence: 99%
“…High chemical scores were demonstrated in Cys, Asp, Thr, Glu, Pro, Gly, His, Lys and Arg; lower scores (Tovar et al, 1989;Bressani et al, 1992;Dodok et al, 1997;Jarošová et al, 1997;Gorinstein et al, 2002 Biological values of protein in untreated and heattreated amaranth grain are summarized in Table 5. High values of chemical scores were found in Lys, Thr, His and Arg.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations